Being as an iceberg: hypertensive treatment adherence experiences in southeast of Iran - Nahid Dehghan Nayeri; Mahlagha Dehghan; Sedigheh Iranmanesh (Taylor & Francis Group, 2015)
Background: Treatment adherence is often an important issue in the management of hypertension. Deep understanding of adherence behavior as well as its influential factors can expand knowledge about treatment adherence among hypertensives. Objective: The aim of this study was to explore patients, their families, and healthcare providers' experiences about hypertension treatment adherence in southeast of Iran. Design: A qualitative study was conducted to explore the experience of patients, family members, and healthcare providers (n=18) by using a conventional content analysis. The purposive sampling method was used. Data were collected through semi-structured and deep interviews. Results: Data analysis showed that hypertensive treatment adherence in an Iranian context is like an iceberg with two subthemes. The first subtheme relates to the upper and clear part of this iceberg and it consists of two categories, including 1) healthy and 2) unhealthy regimens. The second subtheme associates with under-water and unanticipated part and it consists of four categories, including 1) the nature of disease and treatment, 2) the individual resources, 3) the healthcare organization, and 4) the socio-cultural environment. Conclusions: The treatment adherence features emerged in this study can be useful in designing and developing context-based hypertension interventions. Further qualitative and quantitative studies with a closer collaboration between the social, natural, and medical sciences in other Iranian populations are needed to confirm the findings.